PENANGGULANGAN MASALAH SAMPAH PADA MUSIM HUJAN, KKN UNISNU JEPARA MENGADAKAN SOSIALISASI PEMANFAATAN LIMBAH SAMPAH DALAM PEMBUATAN ECOBRICK SD NEGERI BERMI - Nazarudin, Achmad; Amalia, Irsa Dina; Rouf, Abdul; Nailufar, Daniela Arnesti; Mohammad, Gunawan (Jurnal Pengabdian Masyarakat AbdiMas, 2024)
Rainfall increases the problem of waste management in Bermi Village, Mijen District, Demak Regency, causing waste management to be mixed into puddles of water in the school environment, environmental pollution, and health risks for students in carrying out learning activities at Bermi State Elementary School. Effective waste management is important. especially in communities with minimal environmental awareness. The Unisnu Jepara Real Working Group (KKN) held a socialization on the use of waste in making Ecobricks at Bermi State Elementary School. The outreach was carried out to increase students' awareness about waste management in a sustainable way. This research method uses a qualitative approach with the research location at SD Negeri Bermi. Observations, interviews and documentation of activities were carried out during the socialization and creation of Ecobricks. The data was analyzed thematically to identify the effectiveness of activities. This research aims to provide a solution in managing inorganic waste in the Bermi State Elementary School environment and village environments that have not been managed well. The results of the research show that in socialization activities the use of waste in making Ecobricks in Bermi State Elementary School was conducive and students were enthusiastic in participating in the training.